Nursing in Brazil: a sociological perspective on a successful journey (1920-1950) - Castro-Santos, Luiz Antonio de; Castro-Santos, Luiz Antonio de (Revista Brasileira de Sociologia - RBS, 2022)
The article analyses the institutionalization of the nursing profession, by reviewing its historical backgrounds, highlighting the role of the engagement and association between those who propagated new principles and practices for caring, and the professional models that prevailed at different times. It reveals how the professional, cultural and political environment, and especially the degree of State intervention, were jointly responsible for shaping the standards for professional development and labor in each country or region. And then examines the development of the profession in Brazil.